Ácido salicílico em sementes de soja e desempenho de plântulas sob estresse hídrico - Dalcin, Joner Silveira (2019)
Among the challenges faced in soybean production, stress due to water deficit is considered one of the main productivity compromise, being associated with the production of free radicals that cause different damage at the cellular level. To circumvent this situation, a defense mechanism is activated, where salicylic acid plays a key role. Therefore, the objective of this study was (1): to evaluate the physiological quality of commercial soybean seeds submitted to different salicylic acid (SA) concentrations, directly in the germination paper and in gerbox boxes for 24 hours; (2) to evaluate the photosynthetic parameters by stomatal conductance and physiological of soybean seedlings under water stress after imbibition of salicylic acid concentrations in seed germination. In Chapter 1, cultivars NA 5909 RG and Tec Irga 6070 RR were used, which were soaked in different concentrations of salicylic acid in germinating paper and gerbox boxes for 24h and then transferred to germinating paper in the latter case. After 5 days, we determined the number of normal seedlings (first count), length, fresh and dry mass of root and shoots. It was concluded that SA concentrations between 250 and 750 μM can be used in soybean seeds, however, above 1000 μM can impair the physiological quality parameters. In Chapter 2, the Bayer® / Tec Irga 6070 RR cultivar was used, the seeds of which were soaked in 25 ml in salicylic acid (SA) solution for 24 hours under retention capacities of 30, 50 and 70%. In a controlled condition, concentrations of zero, 250; 500; 750 and 1000 μM were adopted, evaluating the variables: length, fresh and dry mass of root and shoot. In a greenhouse, SA concentrations of zero, 500 and 1000 μM were used. After 29 days of sowing, stomatal conductance, length, fresh and dry mass of root and shoot were evaluated. The concentrations of 500 and 1000 μM of AS were efficient in the water deficit for the variables length and root length, fresh and dry mass of the shoot.